1973
DOI: 10.1063/1.1679482
|View full text |Cite
|
Sign up to set email alerts
|

Time dependence of the fluorescence of the B state of CN

Abstract: The alteration of the fluorescence of the B 2Σ state of the CN radical on collisions with foreign gases has been studied by their effect on the decay. A vacuum uv nanosecond flash lamp was used to dissociate the ICN molecule with the direct formation of the CN(B 2Σ). A value for its lifetime extrapolated to zero pressure of the parent gas is 60.8±2.0 nsec. Some gases such as He, Ar, and CF4 do not give any measurable quenching cross section. Others such as Xe appear to quench by promoting the B2Σ → A2Π radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1975
1975
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…The discrepancy is due to the relatively high pressure ͑ϳ500 mTorr͒ of gas used here. In fact, it has been reported that the lifetime of the CN B state measured in a 700 mTorr BrCN vapor is 33 ns, 22 qualitatively consistent with our observation. The combined evidences presented above unambiguously indicate that the observed transient fluorescence is due to free CN(X) radicals produced from the acetyl cyanide photodissociation.…”
Section: A Acetyl Cyanidesupporting
confidence: 93%
“…The discrepancy is due to the relatively high pressure ͑ϳ500 mTorr͒ of gas used here. In fact, it has been reported that the lifetime of the CN B state measured in a 700 mTorr BrCN vapor is 33 ns, 22 qualitatively consistent with our observation. The combined evidences presented above unambiguously indicate that the observed transient fluorescence is due to free CN(X) radicals produced from the acetyl cyanide photodissociation.…”
Section: A Acetyl Cyanidesupporting
confidence: 93%
“…However, the most recent experimental values of Taherian & Slanger (1984;6.67 ± 0.60 μs for v = 2 to 4.3 ± 0.85 μs for v = 5) and Lu et al (1992;6.96 ± 0.3 μs for v = 2 to 3.38 ± 0.2 μs for v = 5) show better agreement, at least for the lower vibrational levels. In contrast, the experimental lifetimes of the B 2 Σ + state obtained in different studies agree reasonably well with each other (Nishi et al 1982;Duric et al 1978;Jackson 1974;Luk & Bersohn 1973).…”
Section: Introductionmentioning
confidence: 36%
“…An earlier calculation by Larsson et al (1983) has provided a value of f 0 0 = 0.0324. Since the experimental lifetimes of the B 2 Σ + state (Nishi et al 1982;Duric et al 1978;Jackson 1974;Luk & Bersohn 1973) agree well with theoretical results (Cartwright & Hay 1982;Larsson et al 1983;Lavendy et al 1984;Bauschlicher & Langhoff 1988), an average value of f 0 0 = 0.033 was adopted by Bakker & Lambert (1998) in their study of the 12 CN and 13 CN lines of the red and violet systems in the spectrum of the post-asymptotic giant branch star HD 56126. Our value of f 0 0 = 0.0337 also supports the value adopted by Bakker & (A color version of this figure is available in the online journal.)…”
Section: The B 2 σ + Statementioning
confidence: 75%
See 1 more Smart Citation
“…The most accurate experimental results are the measurements of the radiative lifetime of the B 2 Σ + state. Low rotational states of the v ′ = 0 level of the B state have measured lifetimes (in ns) of 60.8 ± 2.0 (Luk & Bersohn 1973), 65.1 ± 0.8 (Jackson 1974, and 66.7 ± 1.4 (Duric,Erman & Larsson Table 2: CN Violet System (0,0) with f (0,0) = 0.0330. Derived column densities are given in Table 4.…”
Section: Cn Violet Systemmentioning
confidence: 99%